2017
DOI: 10.25258/phyto.v9i08.9618
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Analysis and Evaluation of In Vitro Anti Oxidant Activity of Punica Granatum Leaves

Abstract: Pomegranate is a large compound of the eastern diets, yet no research has been performed on this product. The pomegranate, Punica granatum belongs to family Lythraceae is an ancient, mystical, unique fruit borne on a small long-living tree cultivated throughout the mediterranean region, as far north as the Himalayas, in Southeast Asia, and in California and Arizona in the United States. Punica granatum is a fruit bearing deciduous herb or small tree growing between 5-8m tall. Punica granatum leaves are used as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 0 publications
5
8
0
Order By: Relevance
“…While P. granatum leaf powder contained Saponins, it was not found in O. europaea. These results are in agreement with previous findings of (Lahmadi et al, 2019), (Shah et al, 2017) and (Boggula and Peddapalli, 2017).…”
Section: Resultssupporting
confidence: 94%
“…While P. granatum leaf powder contained Saponins, it was not found in O. europaea. These results are in agreement with previous findings of (Lahmadi et al, 2019), (Shah et al, 2017) and (Boggula and Peddapalli, 2017).…”
Section: Resultssupporting
confidence: 94%
“…They include P. granatum, P. guajava, C. arborea, G. decora, S. obtusa, and F. hispida. The findings about the potential effectiveness of these plants are similar to those found in the in vivo and in vitro studies previously reported [31][32][33][34][35][36][37][38][39][40]. Leaves from P. granatum and P. guajava and pieces of bark from C. arborea, G. decora, S. obtusa, and F. hispida were collected in Baan Tham, Dok Kham Tai, Phayao.…”
Section: Collection and Preparation Of The Extractssupporting
confidence: 82%
“…Most antiviral studies have been performed on the fruitĘĽs peel and juice, and it has been found that extracts exerted inhibitory activity against HSV-2, HIV-1, and the influenza virus [8][9][10]. Little information has been reported on pomegranate leaf extracts, compared to other edible and nonedible parts of the plant, although some recent studies have indicated that they may be an important source of specialized bioactive metabolites and they possess a broad range of biological properties, such as in vitro antioxidant, anti-inflammatory, anticholinesterase, and antiproliferative activities [5,11,12]. This study explores the cytotoxicity and anti-ZIKV activity of pomegranate leaf ethanolic extracts, as well as of the corresponding fractions and phytoconstituents after a phytochemical and biomolecular characterization of the leaves, which were collected from various sites, after different vegetative periods, and in different years.…”
Section: Introductionmentioning
confidence: 99%